Proline-Catalyzed Asymmetric α-Amination in the Synthesis of Bioactive Molecules - Kumar, Pradeep; Sharma, Brijesh M. (Synlett, 2018)
The direct α-amination of carbonyl compounds using organocatalysts represents a powerful and atom-economical tool for asymmetric C–N bond formation. We describe a complete account of α-functionalization of carbonyl compounds, through iterative sequential α-aminoxylation/amination using electrophilic O and N sources, as well as sequential α-amination/HWE reaction for enantio- and diastereoselective synthesis of both syn- and anti-1,3-aminoalcohols and 1,3-diamines. Additionally this protocol is further extended for the easy construction of alkaloids such as indolizidine, pyrrolizidine, and quinolizidine fused-ring systems just by tuning the chain length of the aldehyde used as a starting material. This methodology provides further scope to extrapolate it for a variety of naturally occurring hydroxylated monocyclic and fused bicyclic pyrrolidine and piperidine based alkaloids such as lentiginosine, epi-lentiginosine, dihydroxypyrrolizidine, (+)-deoxoprosophylline and (–)-deoxoprosopinine alkaloids. Furthermore, we have also uncovered proline-catalyzed anti-selectivity for the synthesis of 1,2-amino alcohols in α-amination of aldehyde and one-pot indium-mediated Barbier type allylation of α-hydrazino aldehydes to accomplish the total synthesis of clavaminols, sphinganine and spisulosine with reduced number of steps and with high overall yields.1 Introduction2 Application in the Total Synthesis of Alkaloids3 Conclusion
Keywords: natural products; alkaloids; organocatalysts; α-amination; C–N and C–O bond formation